Preventing Fraudulent Use of Funds Management Operational Support Education - Saputra, Komang Adi Kurniawan; Dewi, Putu Eka Dianita Marvilianti; Larasdiputra, Gde Deny; Manurung, Daniel T H; Amani, Tatik (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to examine the effect of public participation, proactive supervision, transparency and accountability on the prevention of fraudulent management of school operational funds. The location of the study was conducted in Buleleng Regency, Bali-Indonesia Province with a population of 663 schools in all districts in Buleleng Regency. Data collection techniques with survey methods using a questionnaire. The intended respondents were school leaders throughout the district. Data analysis was performed with multiple linear regression, which resulted that public participation, proactive supervision, transparency and accountability had a positive and significant effect on preventing fraud in the management of school operational assistance funds. The results state that the higher the level of public participation, supervision, transparency and accountability, the better the prevention of fraud.